Comparative genome analysis of Weissella ceti, an emerging pathogen of farm-raised rainbow trout. (December 2015) - Figueiredo, Henrique; Soares, Siomar; Pereira, Felipe; Dorella, Fernanda; Carvalho, Alex; Teixeira, Júnia; Azevedo, Vasco; Leal, Carlos
Abstract Background The genusWeissella belongs to the lactic acid bacteria and includes 18 currently identified species, predominantly isolated from fermented food but rarely from cases of bacteremia in animals. Recently, a new species, designatedWeissella ceti, has been correlated with hemorrhagic illness in farm-raised rainbow trout in China, Brazil, and the USA, with high transmission and mortality rates during outbreaks. AlthoughW. ceti is an important emerging veterinary pathogen, little is known about its genomic features or virulence mechanisms. To better understand these and to characterize the species, we have previously sequenced the genomes ofW. ceti strains WS08, WS74, and WS105, isolated from different rainbow trout farms in Brazil and displaying different pulsed-field gel electrophoresis patterns. Here, we present a comparative analysis of the three previously sequenced genomes ofW. ceti strains from Brazil along withW. ceti NC36 from the USA and those of otherWeissella species. Results Phylogenomic and orthology-based analyses both showed a high-similarity in the genetic structure of theseW. ceti strains. This structure is corroborated by the highly syntenic order of their genes and the neutral evolution inferred from Tajima's D. A whole-genome multilocus sequence typing analysis distinguished strains WS08 and NC36 from strains WS74 and WS105. We predicted 10 putative genomic islands (GEI), among which PAIs 3a and 3b are phage sequences that occur only in WS105 and WS74, respectively, whereas PAI 1 is species specific. Conclusions We identified several genes putatively involved in the basic processes of bacterial physiology and pathogenesis, including survival in aquatic environment, adherence in the host, spread inside the host, resistance to immune-system-mediated stresses, and antibiotic resistance. These data provide new insights in the molecular epidemiology and host adaptation for this emerging pathogen in aquaculture.